Finite-element analysis of hepatic multiple probe radio-frequency ablation - Haemmerich, Dieter; Tungjitkusolmun, Supan; Staelin, S. Tyler; Lee, Fred T.; Mahvi, David M.; Webster, John G. (My University, 2002)
Radio-frequency (RF) ablation is an important means of treatment of nonresectable primary and metastatic liver tumors. RF ablation, unlike cryoablation (a method of tumor destruction that utilizes cold rather than heat), must be performed with a single probe placed serially. The ablation of any but the smallest tumor requires the use of multiple overlapping treatment zones. We evaluated the performance of a configuration incorporating two hooked probes (RITA model 30). The probes were lined up along the same axis in parallel 20 mm apart. Three different modes applied voltage to the probes. The first mode applied energy in monopolar mode (current flows from both probes to a dispersive electrode). The second mode applied the energy to the probes in bipolar mode (current flows from one probe to the other). The third method applied the energy sequentially in monopolar mode (in 2-s intervals switched between the probes). We used the finite-element method (FEM) and analyzed the electric potential profile and the temperature distribution at the end of simulation of a 12-min ablation. The alternating monopolar mode allowed precise independent control of the amount of energy deposited at each probe. The bipolar mode created the highest temperature in the area between the probes in the configuration we examined. The monopolar mode showed the worst performance since the two probes in close vicinity create a disadvantageous electric field configuration. We, thus, conclude that alternating monopolar RF ablation is superior to the other two methods.
Keywords: Ablation; Bipolar ablation; Electrode; Finite-element model; Hepatic ablation; Liver ablation; Radio-frequency ablation; RF ablation